BEDA LUARAN FUNGSI SENSORIMOTOR PASIEN DENGAN DAN TANPA FATIGUE PASCASTROKE ISKEMIK - Maria Putri Utami; Hexanto Muhartomo; Maria Immaculata Widisastuti (NEURONA, 2019)
THE DIFFERENCE OF SENSORIMOTOR FUNCTION OUTCOME IN PATIENTS WITH AND WITHOUT POST ISCHEMIC STROKE FATIGUEABSTRACTIntroduction: Post-stroke fatigue is a burden in improving neurological deficits, rehabilitation, quality of life and capacity at work. Thus, the consequences of post-stroke fatigue should be dealt seriously, considering this is a problem for the patients and difficult to deal with.Aims: To obtain the difference between sensorimotor outcome after ischemic stroke in patients with and without fatigue.Methods: Cohort prospective study of first ischemic stroke patients, conducted at Dr. Kariadi Hospital and Dr. Adhyatma Tugurejo Hospital, Semarang in May-July 2018. Fatigue was determined two weeks post stroke using FACIT-F questionnaire. Sensorimotor outcome was evaluated with Fugl-Meyer Assessment (FMA) two weeks post-stroke and two weeks after the first examination.Results: Among 44 patients with first ischemic stroke, 31.8% patients experienced fatigue and 68.2% patients did not experience it. There was significant sensorimotor outcome difference between patients with fatigue and without fatigue, and also significant variance of sensorimotor outcome difference between those groups.Discussions: Sensorimotor outcome was different between patients with and without post-stroke fatigue. Patients who experienced fatigue had poorer sensorimotor outcome (lower FMA score). They tended to be pessimistic about exercise function and avoided physical activity. Post-stroke fatigue inhibited patient participation in rehabilitation programs and was associated with poor improvement in neurological function.Keywords: FACIT-F, fatigue, Fugl-Meyer Assessment, ischemic stroke, sensorimotor outcomeABSTRAKPendahuluan: Keadaan lelah atau fatigue pascastroke akan menghambat perbaikan defisit neurologis, rehabilitasi, kualitas hidup, dan kapasitas dalam bekerja. Oleh karena itu, konsekuensi fatigue pascastroke harus ditangani secara serius, mengingat hal ini menjadi masalah bagi pasien dan sulit untuk ditangani.Tujuan: Didapatkan perbedaan luaran fungsi sensorimotor pascastroke iskemik pada pasien dengan fatigue dan tanpa fatigue.Metode: Studi kohort prospektif pada pasien stroke iskemik pertama yang dirawat di RSUP Dr. Kariadi dan RSUD Dr. Adhyatma Tugurejo, Semarang pada bulan Mei-Juli 2018. Status fatigue ditentukan 2 minggu pascastroke dengan kuesioner FACIT-F. Luaran fungsi sensorimotor dievaluasi dengan Fugl-Meyer Assessment (FMA) 2 minggu pascastroke dan 2 minggu setelah pemeriksaan pertama.Hasil: Diantara 44 pasien stroke iskemik pertama kali, 31,8% pasien mengalami fatigue dan 68,2% tidak mengalaminya. Adanya perbedaan bermakna luaran fungsi sensorimotor antara pasien dengan fatigue dan tanpa fatigue, juga didapatkan perbedaan bermakna perubahan luaran fungsi sensorimotor antara kedua kelompok tersebut.Diskusi: Luaran fungsi sensorimotor berbeda antara pasien dengan dan tanpa fatigue pascastroke iskemik. Pasien yang mengalami fatigue memiliki luaran fungsi sensorimotor lebih buruk (skor FMA lebih rendah). Pasien dengan fatigue cenderung pesimis akan fungsi olahraga dan menghindari aktivitas fisik. Fatigue pascastroke menghambat partisipasi pasien dalam program rehabilitasi serta berkaitan dengan buruknya perbaikan fungsi neurologis.Kata kunci: FACIT-F, fatigue, Fugl-Meyer Assessment, luaran fungsi sensorimotor, stroke iskemik